The Effect of Illustration on Improving Text Comprehension in Dyslexic Adults. (28th November 2016) - Holmqvist Olander, Mona; Wennås Brante, Eva; Nyström, Marcus
Abstract : This study analyses the effect of pictures in reading materials on the viewing patterns of dyslexic adults. By analysing viewing patterns using eye‐tracking, we captured differences in eye movements between young adults with dyslexia and controls based on the influence of reading skill as a continuous variable of the total sample. Both types of participants were assigned randomly to view either text‐only or a text + picture stimuli. The results show that the controls made an early global overview of the material and (when a picture was present) rapid transitions between text and picture. Having text illustrated with a picture decreased scores on questions about the learning material among participants with dyslexia. Controls spent 1.7% and dyslexic participants 1% of their time on the picture. Controls had 24% fewer total fixations; however, 29% more of the control group's fixations than the dyslexic group's fixations were on the picture. We also looked for effects of different types of pictures. Dyslexic subjects exhibited a comparable viewing pattern to controls when scenes were complex, but fewer fixations when scenes were neutral/simple. Individual scan paths are presented as examples of atypical viewing patterns for individuals with dyslexia as compared with controls. © 2016 The Authors. Dyslexia published by John Wiley & Sons Ltd.